LOWER RESPIRATORY TRACT MICROBIOTA AND ITS SENSITIVITY TO ANTIBACTERIAL AGENTS IN CHILDREN WITH CYSTIC FIBROSIS - Яков Яковлевич Яковлев; Оксана Витальевна Бурнышева; Марина Леонидовна Готлиб; Марина Александровна Пересадина; Ольга Викторовна Лавринова; Анастасия Николаевна Соловьева (The Publishing House Medicine and Enlightenment, 2022)
Cystic fibrosis is an autosomal recessive disease characterized by involvement of all exocrine glands, vital organs and systems. CFTR protein dysfunction leads to chronic infection and subsequent uncontrolled inflammation. Airway infections are associated with a progressive decline in lung function and eventually with respiratory failure, which is the leading cause of death in cystic fibrosis. That's why monitoring of microbiota spectrum in cystic fibrosis patients in some hospitals and research of sensitiveness to antibacterials of prevailing isolated isolates are urgent. The aim of the study - to study respiratory tract microbiota of cystic fibrosis patients of the pulmonology department of Kuzbass Children Clinical Hospital named after prof. Y.E. Malakhovsky (KCCH). Materials and methods. A total of 324 samples from cystic fibrosis patients from 2018 to 2021 were included in the analysis, from which 819 different microorganisms were isolated. Microbiological examination of sputum of cystic fibrosis patients was performed in the bacteriological laboratory of KCCH according to the clinical guidelines «Cystic fibrosis (cystic fibrosis): microbiological diagnosis of chronic respiratory infection». Results. Our study identified the most significant strains of pathogenic flora in children with cystic fibrosis in the pulmonology department of KCCH for the period 2018-2021 - Burkholderia cepacia complex (18.2 %), Staphylococcus aureus (9.5 %) and Pseudomonas aeruginosa (7.9 %). We obtained data on the age dynamics of the microbiota of these patients, indicating an increase in the frequency of Burkholderia cepacia complex and Staphylococcus aureus cultures in adolescence, but a decrease in Pseudomonas aeruginosa. The frequency of bacterial association reaches 73 % and is highest in Burkholderia cepacia complex (57 %).